SPESIFIKASI KEBUTUHAN PERANGKAT LUNAK SISTEM INFORMASI MANAJEMEN ASET DESA - Chandra, Melvin; Setiawan, Rudy (Universitas Ma Chung, 2023)
Sumbersekar village is a village in the Dau sub-district, Malang district. Current asset management is not optimal. So we need an asset management information system that can be used to manage assets in the village so that they are effective. The development of an asset management information system is carried out using the SDLC (Software Development Life Cycle) method at the analysis and design stages. This research aims to create a software requirements specification document that complies with the ISO/IEC/IEEE 29148:2018(E) standard. The design of the asset management information system produces 12 modules, each module has sub modules, namely: master data, planning, procurement, administration, use, utilization, security, maintenance, assessment, deletion, transfer, and reporting. So the results of this research can be used as a guideline in carrying out further developments using the SDLC (Software Development Life Cycle) method so that it becomes an asset management information system that is beneficial for the village.